Determination of Minerals and Trace Elements in Milk, Milk Products, Infant Formula, and Adult Nutrition: Collaborative Study 2011.14 Method Modification. (3rd December 2019) - Cruijsen, Hans; Poitevin, Eric; Brunelle, Sharon L; ,
Abstract: Official Method SM 2011.14/ISO 15151:2018/IDF 229:2018 uses microwave digestion of samples and inductively coupled plasma–atomic emission spectrometry for determination of nine elements, including Ca, Cu, Fe, K, Mg, Mn, Na, P, and Zn. The method was evaluated in a collaborative study of 25 products, including 13 fortified nutritional products (powders, ready-to-feed liquids, and liquid concentrates), five product placebos, six dairy products (liquids, powders, butter, and processed cheese), and the National Institute for Standards and Technology (NIST) Standard Reference Material (SRM) 1849a, in compliance with AOAC INTERNATIONAL Standard Method Performance Requirement (SMPR ® ) 2014.004. This study significantly expanded the applicability of Official Method 2011.14 beyond the original scope of chocolate milk powder, dietetic milk powder, infant cereal, peanut butter, and wheat gluten. The study included 14 collaborators from 11 countries, and results were compared to SMPR 2014.004. Accuracy of the method was demonstrated using NIST SRM 1849a, yielding recoveries across all laboratories of 98–101% for the nine elements. Precision for the 13 fortified nutritional product samples was 2.2–3.9% for repeatability (relative SD of repeatability) and 6.0–12.2% for reproducibility (RSDR ). Excluding Mn, which was present at a wide range of concentrations, the reproducibility was 6.0–9.5%, meeting the performance requirements of SMPR 2014.004. Placebo samples (not fortified with Cu, Fe, Mn, or Zn) yielded acceptable repeatability of 1.8–2.9% for Ca, K, Mg, Na, and P (minerals) but 5.4–29.4% for the low levels of Cu, Fe, Mn, and Zn (trace elements). Reproducibility for the placebos showed the same pattern, with acceptable reproducibility (5.4–10.3%) for minerals but not for the low levels of the trace elements (13.2–82.8%). In the six dairy product samples, repeatability ranged from 1.6 to 3.6% for the minerals, Zn, and the low range of Mn but from 9.4 to 24.6% for Cu, Fe, and the high range of Mn, where concentrations were low as for the nutritional placebos. Reproducibility in the dairy samples was 5.3–8.8% for the minerals but 11.4–55.0% for the trace elements. The mean concentrations of Cu, Fe, and Zn in the dairy products were similar with those in the placebo products, while Zn was present at levels more similar with the fortified nutritional products. Thus, the method met the SMPR criteria except where the trace minerals were present at very low levels. Based on these results, the AOAC Stakeholder Panel for Infant Formula and Adult Nutritionals recommended Final Action status of the expanded applicability of the method. The method was adopted as Final Action by the AOAC Official Methods Board.